Modern methods of breast feeding maintenance in children with intestinal colics. - T. V. Turti; L. S. Namazova-Baranova; I. A. Belyaeva; E. P. Zimina; M. D. Mitish; E. A. Bakovich; N. Y. Savvateeva (Педиатрическая фармакология)
The issue of long-term breast feeding maintenance is relevant for medical communities of many countries of the world. Long-term breast feeding is especially important in premature children and children born with a perinatal pathology. According to scientific literature, the main reasons of breast feeding termination/reduction and early transfer of children to milk formula feeding include impossibility of breast feeding due to condition severity, prematurity, mother’s milk supply failure and, therefore, various functional digestive disorders (aerophagias, regurgitations, flatulence, colics). It is important to ensure proper latching of the baby to the breast, as it is conductive of effective sucking, and recover complete breast feeding in the event of temporary supplementary and mixed feeding. The article presents results of a trial conducted at the FSBI Scientific Center of Children’s Health. Use of special medical products (nipples, phials) developed on the basis of thorough study of maternal breast sucking physiology in the breast feeding termination risk group children (n = 33) allows maintaining children’s need in breast feeding and promotes effective breast feeding recovery.Key words: breast feeding, aerophagia, neonates, premature children, causes of weaning, special medical products (phials, nipples).